Foodways as Highways: Using Food as Cultural Escape - Chi, Jack (Cuizine)

(untitled) (McGill University Library, 2025)
This digital art piece draws inspiration from my own experiences attempting to navigate the interconnectedness of food, culture, and queerness, as well as two pieces examining immigrant food experiences. Anita Mannur’s “Perfection on a Plate: Readings in the South Asian Transnational Queer Kitchen” relates queerness and food in an analysis of the film Nina’s Heavenly Delights, and Tulasi Srinivas’s "’As Mother Made It': The Cosmopolitan Indian Family, ’Authentic' Food and The Construction of Cultural Utopia” focusses on the unique experiences of the children of immigrants. In this piece, the girl flees heteronormativity in favor of queerness; simultaneously, she flees traditional Chinese foods in favour of Canadian fare. It is representative of the internal conflict experienced by immigrants and children of immigrants as they are torn between cultures, and the intrinsic links between food and culture. The girl strides across the chasm on a path of shattering plates, using food and foodways to deny her Chinese cultural identity. Though she takes this path willingly, she still weeps for the culture she is forced to leave behind. The relationships between culture, food, and queerness are undeniable but complex, and exploring these relationships is a journey unique to each individual. This art piece highlights the way in which food can serve as a cultural escape and attempts to represent my personal experience as the queer, rebellious child of an immigrant.